2012
DOI: 10.3109/14992027.2012.705900
|View full text |Cite
|
Sign up to set email alerts
|

A replication study on proposed candidate genes in Ménière's disease, and a review of the current status of genetic studies

Abstract: Our review of the reported candidate genes shows that the current understanding of the genetic factors contributing to the development of MD is limited, and that the study of its etiology would benefit greatly from more comprehensive genetic knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 36 publications
1
13
0
1
Order By: Relevance
“…Quite recently a possible linkage to chromosome 5 and a second locus on chromosome 12 were observed in an analysis of 17 German FMD families [3]. Several inconclusive candidate gene studies with regard to MD have been performed [12], but no predisposing genetic factors have been identified. Modern genetics, genome-wide association and next generation sequencing studies, nevertheless promise a great deal with regards to discovering the origin of MD.…”
Section: Introductionmentioning
confidence: 97%
“…Quite recently a possible linkage to chromosome 5 and a second locus on chromosome 12 were observed in an analysis of 17 German FMD families [3]. Several inconclusive candidate gene studies with regard to MD have been performed [12], but no predisposing genetic factors have been identified. Modern genetics, genome-wide association and next generation sequencing studies, nevertheless promise a great deal with regards to discovering the origin of MD.…”
Section: Introductionmentioning
confidence: 97%
“…Campbell et al 73 found no association in the Caucasian population and could not duplicate the Doi results. In a more recent study of Hietikko et al 74 the genotype with the A-allele seemed to protect against SMD. However, they found four novel sequence variations in the KCNE1 gene in three SMD and one FMD patient, the mutation seems to be disease causing but needs a larger sample to be confirmed.…”
Section: Candidate Genes Association Studiesmentioning
confidence: 87%
“…The real problem is that most of these studies analyzed familial and sporadic patients together, and principally, that no positive replications of previously described candidate genes have been reported. Actually, a recent study of Hietikko et al 74 reports on the screening of previously MD associated genes AQP2, KCNE1, KCNE3, COCH, HCFC1 , and ADD1 on 59 individuals (38 sporadic and 21 independent FMD samples) with a control population of 98 persons. Only rs1805127 ( KCNE1 ) remained significant after correction for multiple testing.…”
Section: Candidate Genes Association Studiesmentioning
confidence: 99%
“…However, most of the SNPs had small effect size with an odds ratio <2, and several variants were located in the noncoding regions of the genome. In addition, none of them would be replicated among a different ethnic group (26,44,45). These suggest that a common genetic variant cannot explain the entire heritability of MD and another investigation may be needed (46).…”
Section: Discussionmentioning
confidence: 98%